ANALISIS PENGARUH BRAND EXPERIENCE KULINER KOREA DAN PERCEIVED VALUE TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN: ANALISIS KUANTITATIF PADA PELANGGAN OMEN CHIKIN - Febi Gilianto; Muryati, Muryati; Nasharuddin Mas (Jurnal Cakrawala Ilmiah, 2024)
The aim of this research is to analyze the influence of Korean culinary brand experience and perceived value on customer loyalty through customer satisfaction: quantitative analysis of Omen Chikin customers. This research uses a quantitative research design. The type of research used is to explain the causal relationship between research variables through testing hypotheses that have been previously formulated. The population in this study is the unknown number of Korean culinary customers, Omen Chikin, Malang City. The lemeshow formula was used to determine the sample size, and rounded it up to 100 respondents. The sampling technique used was nonprobability sampling with the technique taken being purposive sampling. The analysis model used is the Structural Equation Model with the help of SmartPLS version 4. The research results show that a better brand experience can encourage increased customer loyalty. Even though the brand experience is getting stronger, it is not able to increase customer satisfaction. Even though perceived value is getting stronger, it is not able to encourage increased customer loyalty. Better perceived value can encourage increased customer satisfaction. Higher customer satisfaction can encourage increased customer loyalty. Customer satisfaction is unable to play a role in mediating the indirect influence of brand experience on customer loyalty. Customer satisfaction is able to play a role in fully mediating the indirect influence of perceived value on customer loyalty.